The Challenges of Public Participation in the Malaysian Planning System - Marlyana Azyyati, Marzukhi; Jamalunlaili, Abdullah; Oliver Ling, Hoon Leh; Khalid, Zanudin; Muhammad Hakim, Danial (Malaysian Institute of Planners, 2022)
This study provides an overview of the development of Malaysia’s planning system, particularly in relation to public participation. A case study of Malaysia is critical as this study highlights the challenges in planning practice, thereby presenting a critical reflection of planning experiences in response to a specific context. Specifically, this study aims to assess how the public participation process operates within the mechanisms of the planning system, including the challenges presented to the Malaysian planning practice. This study was conducted at Gasing Hill in the Federal Territory of Kuala Lumpur. Secondary data were gathered by performing an in-depth interview with 20 respondents. The findings revealed how planners deal with the public concerning the formation of the Gasing Hill case. The planners had been given the privilege to take decisions governing the consultative process. Thus, understanding the roles and responsibilities of planners is necessary if the practices that epitomise the ethos of participatory democracy in Malaysia are to be changed. This study adds to the growing literature that suggests the importance of public participation in shaping the future development of Malaysia.